Making minds less well educated than our own - Schank, Roger C., 1946-2023 (Lawrence Erlbaum, 2004)
In the author's words: "This book is an honest attempt to understand what it means to be educated in today's world." Schank's argues that no matter how important science and technology are, as a society we believe that those educated in literature, history and other humanities are more worthy of the descriptor "well educated."